Synovial fluid and plasma levels of milk fat globule–epidermal growth factor 8 are inversely correlated with radiographic severity of knee osteoarthritis. Issue 9 (September 2019) - Chen, Feihu; Liu, Hao; Xia, Jie; Ding, Xiaomin; Fan, Jianbo; Zhu, Xinhui; Cui, Shengyu; Yi, Hong; Gao, Rufeng; Liu, Wei
Objective: Mounting evidence demonstrates that inflammation plays an important role in the pathogenesis of osteoarthritis (OA). Milk fat globule–epidermal growth factor 8 (MFG-E8) is an important glycoprotein that is involved in anti-inflammatory responses. The present study was performed to assess the MFG-E8 levels in plasma and synovial fluid and explore the association between radiographic severity and MFG-E8 levels in patients with knee OA. Methods: This study involved 138 healthy controls and 142 patients with knee OA. The MFG-E8 levels in plasma and synovial fluid were evaluated by enzyme-linked immunosorbent assay. The Kellgren and Lawrence classification was used for OA grading. Results: The plasma MFG-E8 level was significantly lower in patients with knee OA than in healthy controls. The synovial fluid MFG-E8 level was significantly lower than the plasma level in patients with knee OA. More importantly, the MFG-E8 levels in synovial fluid and plasma were significantly and inversely associated with radiographic severity among patients with knee OA. Conclusions: These results demonstrate that the levels of MFG-E8 in synovial fluid and plasma are inversely correlated with the radiographic severity of knee OA.